KAJIAN SISTEM ALIRAN PADA DAERAH ALIRAN SUNGAI (DAS) BENDUNG KOTA PALEMBANG - Arfy, Muhammad Caisar; Yunus, Ishak; Kasmuri, Mudiono (Civil Engineering Study Program Faculty of Engineering, University of Palembang, 2019)
Bendung River is one of the nine Musi River’s streams located in Palembang. Its estuary is located on Jalan SlametRiyadi 10 ilir, Ilir Timur II Palembang. This river is affected by the annual cycle of the rainy season on September until April. The width of the drainage area of this Bendung river 15,4km2 and it is one of the rivers where flood often occurs. Based on the analysis which was done in the area of Kuto Bendung river in Palembang, the velue of the planning rain debit for ten years was 1,683m3/sec and the largest existing debit was 2,330m3/sec for S1 and S2 waterways, and 1,432m3/sec for S3 and S4 waterways. Thus, there should be further studies to solve the problem well or the correct way by making the dimension becomes larger or fixing it.